PENERAPAN PEMBELAJARAN DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X IPA.2 SMA NEGERI 1 UJUNGBATU - Setiyaningsih, Wiwik; Maimunah, Maimunah; Siregar, Syarifah Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was based on students’ mathematics learning outcomes of class X Science2 at Senior High School 1 Ujungbatu which still under the Minimum Criteria of mastery learning (KKM) that has been settled by the school that is 75. Based on the data of quiz (UH) on absolute-value equation and inequalities topic, there were 92% students who didn’t reach KKM. The purpose of this research was to improve the learning process and the students’ mathematic learning outcomes at class X Science.2 of Senior High School 1 Ujungbatu at the first semester in 2017/2018 academic year on rational and irrational inequalities topic, and linear equation system of three variables topic. This research was classroom action research with two cycles. The instruments used in this research were learning devices and the instruments of collecting data. The learning devices used were syllabus, lesson plan (RPP), and student woksheet (LKS). While the instruments of collecting data were observation sheets and students mathematic test. The observation sheets were used to find out the data of students and teacher activity during learning process which would analyzed qualitatively, and students mathematic test were used to collect the students’ mathematic learning outcomes which would analyzed quantitatively. The subject of this research was the students at class X Science.2 of Senior High School 1 Ujungbatu 2017/2018 academic year which consisting of 13 boys and 23 girls with heterogeneous ability. Based on the analyzed of students and teacher activity after implemented the scientific learning approach, it can be concluded that there was an improvement of learning process at each cycles. The analyzed of students’ mathematic learning outcomes data shows that there was an improvement of students’ mathematic learning outcomes in second cycle. There were 8% students that reach KKM in UH I, and its improved in UH II which 28% students who reach KKM. Based on the result above, it can be concluded that the implementation of scientific learning approach can improve the learning process and the students’ mathematic learning outcomes at class X Science2 of Senior High School 1 Ujungbatu.Key Word: Mathematic learning outcomes, scientific learning approach, classroom actionresearch